Bungo stray dogs. 05 - Asagiri, Kafka (Yen Press, 2017)
"As Kyouka fights her past demons, the threat of a three-way war between the Armed Detective Agency, the Guild, and the Port Mafia looms. With each side fortifying their defenses, who will seize the initiative and land the first crushing blow? After an attack by the Guild's fellowcrafts, the Agency's chances for survival might just be gone with the wind ..."--Page 4 of cover.